TINJAUAN PUSTAKA: PERANCANGAN SISTEM PENDINGIN TERMOELEKTRIK BERTENAGA SURYA DAN RAMAH LINGKUNGAN - Enrico Chiesa Virgianto; Oktarina Heriyani (Fakultas Teknik, Universitas Muhammadiyah Prof. Dr. Hamka, Jakarta, 2025)
The growing demand for environmentally friendly cooling technologies has encouraged the use of thermoelectric systems based on the Peltier effect as an alternative to conventional vapor-compression systems that rely on harmful refrigerants. This research focuses on designing a portable cooling device powered by solar-generated electricity to create an efficient and sustainable refrigeration solution. The system integrates solar panels, a battery, a TEC module, a heatsink, a coldsink, and cooling fans to ensure effective heat dissipation. Performance evaluation was conducted through three experimental tests by calculating the Coefficient of Performance (COP) and analyzing convective heat transfer using Reynolds number, friction factor, Nusselt number, and heat flux. The results show that solar intensity plays a key role in determining the electrical power supplied to the thermoelectric module, thus influencing its cooling performance. COP values varied across the trials, with the highest average value of 0.167944 recorded in the third test. Although its efficiency remains lower than that of vapor-compression systems, the prototype demonstrates that a solar-powered thermoelectric cooler can serve as an energy-efficient, refrigerant-free, and environmentally friendly portable cooling solution.